SYMBOLIC INTERACTION IN THE TRADITIONAL WEDDING CEREMONY OF THE PEOPLE OF TEMPIRAI VILLAGE, PALI DISTRICT - Okti Tersani Tersani; Muhammad Iqbal Birsyada (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research is motivated by the tradition of the wedding ceremony of the Tempirai village community which is unique in no other place and the existence of symbolic interactionism in the traditional wedding ceremony so that it is interesting to study. This research aims to find out the series of traditional wedding rituals of the Tempirai Village community, as well as the role of symbolic interactionism in the ceremony. This research uses a qualitative approach through the use of case study methodology. Data collection methods were conducted through observation, in-depth interviews, and documentation. This research uses data reduction, data presentation, and conclusion drawing as its data analysis approach. The results of this study show that the traditional marriage ceremony procession of the Tempirai village community begins with the process of gathering the nuclear family, proposal, invitation notification, mipis bumbu, simbang ngambik, marriage contract, mapak, and tandang sujud. Secondly, the process of symbolic interactionism in the traditional marriage ceremony in Tempirai community includes the procession of making a basket by the groom-to-be, the process of invitation notification with mokon, and sen jujur or the bride-to-be's request to the groom-to-be.